The transmission of visceral leishmaniasis in the municipality of Guarujá, on the Coast of São Paulo state, Brazil - Casanova, Claudio; Motoie, Gabriela; Domingos, Maria de Fátima; Silva, Vanessa Gusmon da; Silva, Mariana Dantas da; Galati, Eunice Aparecida Bianchi; Galvis-Ovallos, Fredy (Revista de Saúde Pública, 2022)
OBJECTIVE: To perform an entomological survey, evaluating the circulation of Leishmania spp. in sand flies captured from the new foci of visceral leishmaniasis (VL) in the coastal region of São Paulo state. METHODS: Sand flies were captured from November 2016 to September 2018 using light traps of the Centers for Disease Control (CDC), in the neighborhood where VL cases were reported. Leishmania spp. circulation was evaluated by gut dissection and molecular analysis of the females captured. RESULTS: Nyssomyia intermedia was the more frequent species (90,7%) within the 1,203 sand flies captured. We found no flagellates in dissected females, but two pools containing females of Ny. Intermedia presented DNA of L. infantum. CONCLUSION: Our results suggest that Ny. intermedia might be involved in the establishment of this new VL focus in Sao Paulo. However, before incriminating this species as a L. infantum vector, further studies should investigate other vectorial capacity parameters, including competence, survival, and feeding habits.